1993
DOI: 10.1073/pnas.90.20.9295
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Tetrahymena thermophila by microinjection of a foreign gene.

Abstract: Tetrahymena thermophila has been transformed to paromomycin-resistant phenotypes by microinjec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 31 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…To test whether the MTT1 promoter can induce the expression of other coding regions in response to cadmium, a reporter construct was made by replacing the MTT1 coding region with the neo1 coding region which confers paromomycin (pm) resistance when expressed in Tetrahymena macronuclei (11). Because this reporter gene is flanked by MTT1 noncoding sequences, it integrates into the MTT1 locus by homologous recombination when biolistically transformed into Tetrahymena.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether the MTT1 promoter can induce the expression of other coding regions in response to cadmium, a reporter construct was made by replacing the MTT1 coding region with the neo1 coding region which confers paromomycin (pm) resistance when expressed in Tetrahymena macronuclei (11). Because this reporter gene is flanked by MTT1 noncoding sequences, it integrates into the MTT1 locus by homologous recombination when biolistically transformed into Tetrahymena.…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with the introduction of heterologous drug-resistance gene markers (11,12), these methods enabled facile gene replacement, allowing gene disruption (13) and insertion of mutant genes with flanking selectable markers (14). They also led to techniques for transformation of the germ-line micronucleus which, again, occurs by homologous integration (15).…”
mentioning
confidence: 99%
“…H2A1 and H2A2 proteins are not detectable in the HTA1-and HTA2-disruptive transformants, respectively. The unlabeled, fastestmigrating band comigrates with histone H4, whose amino-terminal sequence is similar to that of hv1 (2 However, in this report, using newly developed transformation and gene replacement techniques (13)(14)(15)21), we demonstrated that, although the HTA1 or HTA2 gene, encoding the major H2A subtypes, can be completely knocked out, the HTA3 gene can be only partially replaced. Thus, in T. thermophila, the HTA3 gene encoding H2A variant hv1 is essential for vegetative growth.…”
Section: Discussionmentioning
confidence: 95%
“…They were then transferred to media containing increasingly higher concentrations of drug. The highest concentration of paromomycin tolerated by these transformants is defined as the maximum drug concentration at which cells can divide at least once each day, as described elsewhere (21). Table 1 summarizes these results.…”
Section: Transformation In T Thermophilamentioning
confidence: 87%
See 1 more Smart Citation